STRATEGI GURU MEMOTIVASI PESERTA DIDIK DALAM BELAJAR MEMBACA ALQURAN DI TPA NURUL IMAN AIR PUTIH JORONG IVKOTO NAGARI KINALI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Dermawati Dermawati; Khairuddin Khairuddin (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by a phenomenon that students often have difficulty in learning to read the Qur'an. This has an impact on the decline in students' learning motivation towards their ability to read the Qur'an. Therefore, it is necessary to have a special strategy from the teacher to increase the learning motivation of students in learning to read the Qur'an. The approach used in this study is a qualitative approach. The research location is located at the TPA Nurul Iman Air Putih Jorong IV Koto. The data that the researchers got from the Al-Qur'an teacher (who teaches students to read the Qur'an) and students. The method used is observation, interviews and documentation. The results of the study revealed: (1) The strategy of the Al-Qur'an teacher through an individual approach, namely the teacher took an individual approach by approaching students one by one. The teacher must recognize the character of each individual, because each individual has different characters and abilities, the teacher must be able to present it in a language that is understood by students. (2) The strategy of the Al-Qur'an teacher through the provision of sanctions, namely punishment is only in the form of bluffing to make students deterrent and not feel that they are being punished. Teachers are very careful in giving punishment, usually by telling students to memorize. However, if students are not deterred, they will be given the same punishment again. 3) The strategy of the Al-Qur'an teacher through providing guidance is by taking an individual approach first to find out and explore the character of students, the personality of students, and the problems that students complain about. Keyword: Teacher Strategy, Learning Motivation